2010
DOI: 10.1017/s1047951110001514
|View full text |Cite
|
Sign up to set email alerts
|

QT dispersion in childhood obstructive sleep apnoea syndrome

Abstract: The difference between maximal and minimal QT interval and corrected QT interval defined as QT dispersion and corrected QT dispersion may represent arrhythmogenic risks. This study sought to evaluate QT dispersion and corrected QT dispersion in childhood obstructive sleep apnoea syndrome. Forty-four children (34 male) with obstructive sleep apnoea syndrome, aged 6.2 plus or minus 3.5 years along with 38 healthy children (25 male), 6.6 plus or minus 2.1 years underwent electrocardiography to measure QT and RR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Several studies in children have previously demonstrated an association between increased resting QTd and various conditions. Although most studies demonstrated an association with arrhythmia [8,11,36], QTd was also reported in conditions without arrhythmia, such as acute rheumatic carditis [10], obesity [29], sleep apnea [21], and type 1 diabetes [34]. The absence of CA disease in these pediatric reports corroborate with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies in children have previously demonstrated an association between increased resting QTd and various conditions. Although most studies demonstrated an association with arrhythmia [8,11,36], QTd was also reported in conditions without arrhythmia, such as acute rheumatic carditis [10], obesity [29], sleep apnea [21], and type 1 diabetes [34]. The absence of CA disease in these pediatric reports corroborate with our findings.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, documented data for the relation of respiratory disorders and cardiovascular diseases related to sleep also indicate the arrhythmogenic properties of the sleep related respiratory diseases. In the current study done by Khositseth et al (11) QT dispersion and corrected QT dispersion values were higher in children with OSAS compared to normal population. As known in general, QT dispersion points to arrhythmogenic potential (12).…”
Section: Discussionsupporting
confidence: 44%
“…Apneic bradycardia and postvagal tachycardia that occurs later on compose the occult additional diagnostic findings that was on the telemetric ECG recordings (28). Upon the increase of the knowledge on the analysis of ECG data using different analytic methods could be helpful in recognizing of the sleep related respiratory disturbances, recent studies investigating the availability of ECG in OSAS screening have focused on the analysis of the different segments of ECG such as QT dispersion and the contribution of various algorithms to the diagnosis (11). Current studies for the OSAS survey evaluating different algorithms and data from these algorithms from the spectral analysis of one channel ECG due exist.…”
Section: Discussionmentioning
confidence: 99%
“…QTd is another marker of cardiac repolarization abnormality and risk of SCD. Several recent studies have reported increased QTd in adults and children with OSA [35,50]. Therefore, measurements of QTd in OSA patients might identify the risk of arrhythmias in these patients.…”
Section: Discussionmentioning
confidence: 99%